2009
DOI: 10.5539/elt.v2n1p13
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Incidental Vocabulary Acquisition: A Case on Narrative and Expository Texts

Abstract: This study was intended to determine whether or not the genre of a reading text affects the incidental vocabulary acquisition of L2 learners while reading. To this aim, 40 Iranian EFL students whose vocabulary knowledge was within a limited range (already determined by Nation's Vocabulary Levels Test) were divided into two groups of 20 each for the reading sections. The Narrative Group comprised the participants who read the narratives, and the Expository Group were those who read the expository texts. Three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…These conclusions are also supported by findings from studies on the impact of text genre, where the more demanding genre (expository) was found to contribute more to incidental vocabulary acquisition compared with the narrative genre which is perceived as easier with respect to text comprehension (e.g. Shokouhi & Maniati, 2009).…”
Section: Discussionsupporting
confidence: 61%
“…These conclusions are also supported by findings from studies on the impact of text genre, where the more demanding genre (expository) was found to contribute more to incidental vocabulary acquisition compared with the narrative genre which is perceived as easier with respect to text comprehension (e.g. Shokouhi & Maniati, 2009).…”
Section: Discussionsupporting
confidence: 61%
“…However, according to Shokouhi (2009), most vocabulary is acquired incidentally later on in the learning process since it occurs as a result of other activities -especially those related to reading, intensive or extensive. This was also emphasized by Nation (1997) who maintained that by involving the learners in listening or reading comprehension tasks, teachers can help promote their students' incidental vocabulary learning.…”
Section: Introductionmentioning
confidence: 99%
“…This is true also for Hanauer (2001a), who focused on L2 readers. Furthermore, studies on IVA during reading that considered genre in their study did not take into account findings from literary theory when designing and evaluating their studies (e.g., Shokouhi & Maniati, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The process of “picking up” a new word has been shown to be frail and dependent on a large number of factors, for instance, various context properties (Bordag, Kirschenbaum, Opitz, & Tschirner, 2015; Webb, 2008), topic familiarity (Pulido, 2003), exposure frequency (Godfroid et al, 2017; Pellicer-Sánchez, 2016; Rott, 1999), or salience of the word form (Rieder, 2002a, 2002b). Text genre has been identified as one such factor (Shokouhi & Maniati, 2009; Taylor & Beach, 1984; Moore & Zabrucky, 1999). Shokouhi and Maniati report evidence that expository texts resulted in superior gains than narrative texts in the early stages of vocabulary acquisition.…”
Section: Background and Significancementioning
confidence: 99%